2022
DOI: 10.3390/biom12111617
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 as a Prognostic Factor and Its Immune Implication with Molecular Characterization in Prostate Cancer: An Integrated Multi-Omics in Silico Analysis

Abstract: Prostate cancer (PCa) is a type of potentially fatal malignant tumor. Immunotherapy has shown a lot of potential for various types of solid tumors, but the benefits have been less impressive in PCa. Enhancer of zeste homolog 2 (EZH2) is one of the three core subunits of the polycomb repressive complex 2 that has histone methyltransferase activity, and the immune effects of EZH2 in PCa are still unclear. The purpose of this study was to explore the potential of EZH2 as a prognostic factor and an immune therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…The study revealed that EZH2 may be an effective predictor of PCa prognosis and immune response. 203 Similar results of histone lysine methylation (HLM) regulators ((EZH2, NSD2, and KMT5C) found in an analysis of The Cancer Genome Atlas (TCGA)-PRAD dataset. 204 Another study also observed a strong connection between EZH2 expression and macrophage infiltration in breast cancer, suggesting that modulating epigenetic regulation to control macrophage activation is a potential therapeutic strategy for breast cancer.…”
Section: Histone Modificationsupporting
confidence: 53%
“…The study revealed that EZH2 may be an effective predictor of PCa prognosis and immune response. 203 Similar results of histone lysine methylation (HLM) regulators ((EZH2, NSD2, and KMT5C) found in an analysis of The Cancer Genome Atlas (TCGA)-PRAD dataset. 204 Another study also observed a strong connection between EZH2 expression and macrophage infiltration in breast cancer, suggesting that modulating epigenetic regulation to control macrophage activation is a potential therapeutic strategy for breast cancer.…”
Section: Histone Modificationsupporting
confidence: 53%